1997
DOI: 10.3354/meps148049
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive patterns and population characteristics in five deep-water pandalid shrimps in the Western Mediterranean along a depth gradient (150-1100 m)

Abstract: ABSTRACT. Reproductive patterns and populations characteristics of 5 deep-water pandalid shrimp species of the genus Plesionika (Decapoda: Caridea) were studied between 150 and 1100 m depth in the Western Mediterranean Sea over the period 1991 to 1994, including monthly samples taken from November 1992 to October 1993. With the aim of establishing interspecific relationships among reproductive biology and population characteristics 2831 individuals of Plesionjka hetel-oca~pus, 1787 of P edwardsl, 1601 of P. gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 21 publications
(38 reference statements)
8
61
2
1
Order By: Relevance
“…In addition, the seasonal differences in species of the genus Plesionika can be related to their reproductive pattern. The major abundance of P. edwardsi and P. martia during autumn could be due to the fact that their maximum reproduction occurs during spring and summer (Company and Sardà, 1997), which therefore leads to the subsequent recruitment of these species in autumn. Recruitment could also be on the basis of the predominance in spring of M. merluccius, a species that in the northwestern Mediterranean shows a maximum recruitment during this season (Maynou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the seasonal differences in species of the genus Plesionika can be related to their reproductive pattern. The major abundance of P. edwardsi and P. martia during autumn could be due to the fact that their maximum reproduction occurs during spring and summer (Company and Sardà, 1997), which therefore leads to the subsequent recruitment of these species in autumn. Recruitment could also be on the basis of the predominance in spring of M. merluccius, a species that in the northwestern Mediterranean shows a maximum recruitment during this season (Maynou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…More difficult to ascertain, however, are the reasons behind such a pattern in an environment of constant food supply and devoid of any marked seasonality. In general, little is known about the endogenous or exogenous factors that control reproductive cycles in the deep sea (Company & Sarda 1997). Schoener (1968) first suggested that variation in the flux of particulate food material to the deep sea might cue seasonality in reproductive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Tyler 1988, Gage & Tyler 1991, Company & Sarda 1997. However, it was in 1920 that Orton first introduced the hypothesis that, because the physical environment in the deep sea does not experience seasonal temperature variation, the breeding period of deep-sea species would be expected to be continuous throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…Why is the only species without a clear seasonality to its reproductive processes blind? Why is this species the only one with differently coloured gonads and eggs, while all the others follow a similar trend in relation to the colour of their gonads and exoskeletons (Company 1995)? However the main question is: if, as mentioned in the first section of this discussion, the available energy at middle-slope depths does not allow species to undertake year-round reproductive processes, why does Polychele typhlops do this?…”
Section: Timing Of Reproductive Processes Of Deep-water Mediterraneanmentioning
confidence: 99%
“…Relationship between reproductive periods, first appearance of juveniles and egg size/number/colour among decapod crustaceans dwelling in the deepest bathymetric range sampled in this study (between 600 and 1100 m depth). Species are ordered, from left to right, following the phylogenetic classification shown in Table 1 Company (1995); f this study; g this species does not carry eggs (Demestre & Fortuño 1992); h egg size and egg number is indicated as a relative value when compared only between the species of the table;…”
Section: Biological Traits Related To the Timing Of The Reproductive mentioning
confidence: 99%